Airflow measurement across negatively infiltration processed porous aluminum structures. Issue 4 (17th January 2019) - Otaru, A. J.; Morvan, H. P.; Kennedy, A. R.
Abstract : Detailed structural characterization and experimental measurement of airflow across open‐celled aluminum foam structures with near‐spherical cells varying in pore sizes and interstices are presented herein. The aluminum foam structures were produced by infiltrating liquid aluminum into convergent gaps created by packed beds of near‐spherical hydrosoft salt beds varying in particle sizes, packing densities, and infiltration pressures. A quantitative assessment of the unit pressure drops developed across these structures show that viscous and inertial terms of these structures were observed to greatly depend on the shape and structural macroscopic parameters of the porous medium. © 2019 American Institute of Chemical Engineers AIChE J, 65: 1355–1364, 2019